SIMULATION OF 1D-PSEUDOHOMOGENEOUS MODEL OF FIXED BED FISCHER-TROPSCH REACTOR USING BIOSYNGAS - Alwi Ash Shiddiq, Rasyid
Fossil fuels, especially petroleum, are the main source of energy in Indonesia. Based on BP Global Company data, in 2019 oil consumption reached 1.8 million bpd. Since petroleum is a non-renewable energy source, it is important to switch to environmentally friendly energy sources. One method of fuel oil production is Fischer-Tropsch (FT) synthesis. In order to produce an environmentally friendly product, a feed in the form of biomass gasification synthesis gas called biosyngas is used. This study aims to build a FT reaction model and determine the effect of operating conditions on FT simulation results. The Fischer-Tropsch reactor built in this study is a fixed bed reactor in a 1D pseudo-homogeneous model with biosyngas feedstock (33% H2, 17% CO, and 50% N2). The simulation process of the Fischer-Tropsch reactor model was performed using MATLAB software at operating conditions of 20 bar and 473 K. The first operating condition varied was the Gas Hourly Space Velocity (GHSV) at values of 50, 100, 150, and 200 Nml.gcat-1h-1. The highest CO conversion was 66.36% at GHSV 37 Nml.gcat-1h-1 and the highest H2 conversion was 66.82% at GHSV 37 Nml.gcat-1h-1. C1-C4 selectivity values tended to increase, while C5+ selectivity decreased. The second operating condition varied was the H2/CO ratio in the feed at values of 1.0, 1.5, 2.0, and 2.5. The highest CO conversion was 70.35% at a ratio of 2.5 and the highest H2 conversion was 58.45% at a ratio of 1.5. The high ratio caused the selectivity of short-chain hydrocarbon products to increase. The third operating condition varied was the wall temperature (Tw) at 473K, 483K, and 493K. The highest CO and H2 conversions were obtained at the highest Tw with values of 88.54% and 86.30% respectively. High Tw causes the selectivity of short-chain hydrocarbons to increase.